Fast and cost-effective cyclotron production of 61Cu using a natZn liquid target: an opportunity for radiopharmaceutical production and R&D. Issue 42 (13th July 2017) - do Carmo, S. J. C.; Alves, V. H. P.; Alves, F.; Abrunhosa, A. J.
Abstract : Following our previous work on the production of radiometals, such as 64 Cu and 68 Ga, through the irradiation of liquid targets using a medical cyclotron, we describe in this paper a technique to produce 61 Cu through the irradiation of natural zinc using a liquid target. Abstract : Following our previous work on the production of radiometals, such as 64 Cu and 68 Ga, through the irradiation of liquid targets using a medical cyclotron, we describe in this paper a technique to produce 61 Cu through the irradiation of natural zinc using a liquid target. The proposed method is very cost-effective, as it avoids the use of expensive enriched material, and is fast, as a purified solution of 61 CuCl2 is obtained in less than 30 min after the end of beam. Considering its moderate half-life of 3.33 h and favourable decay properties as a positron emitter, 61 Cu is a very attractive nuclide for the labelling of PET tracers for pre-clinical and clinical use with PET as well as to support the intense R&D programmes being carried out worldwide by taking advantage of the rich and versatile chemistry of copper.